2011
DOI: 10.1016/j.ajpath.2011.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Relevance of IgG and IgM Antibodies against Desmoglein 3 in Blister Formation in Pemphigus Vulgaris

Abstract: Pemphigus vulgaris is an autoimmune disease caused by IgG antibodies against desmoglein 3 (Dsg3). Previously, we isolated a pathogenic mAb against Dsg3, AK23 IgG, which induces a pemphigus vulgaris-like phenotype characterized by blister formation. In the present study, we generated a transgenic mouse expressing AK23 IgM to examine B-cell tolerance and the pathogenic role of IgM. Autoreactive transgenic B cells were found in the spleen and lymph nodes, whereas antiDsg3 AK23 IgM was detected in the cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 39 publications
0
51
0
2
Order By: Relevance
“…However, our immunoprecipitation experiments also revealed that the complex is not detectable exclusively in the soluble pool but also within desmosomes. Moreover, AK23, which induces p38 MAPK activation (20), has been shown to also bind to Dsg3 within desmosomes (42). Thus, the contribution of desmosomal versus non-desmosomal Dsg3 to signaling events needs to be clarified further.…”
Section: Dsg3mentioning
confidence: 99%
“…However, our immunoprecipitation experiments also revealed that the complex is not detectable exclusively in the soluble pool but also within desmosomes. Moreover, AK23, which induces p38 MAPK activation (20), has been shown to also bind to Dsg3 within desmosomes (42). Thus, the contribution of desmosomal versus non-desmosomal Dsg3 to signaling events needs to be clarified further.…”
Section: Dsg3mentioning
confidence: 99%
“…Antibody attachment causes interference in cell-to-cell adherence that ultimately leads to keratinocyte acantholysis, resulting in an intraepithelial blister (1,2). Any epidermal area, both mucosal and cutaneous, can be affected.…”
mentioning
confidence: 97%
“…After the second immunization, the main antibodies are IgG. (20) Usually the interval time of the first and second immunizations was 2-3 weeks. If the interval time between them was too short, the concentration of IgM would be greater.…”
Section: Resultsmentioning
confidence: 99%